SGLT2i reduce arrhythmic events in heart failure patients with cardiac implantable electronic devices - Marco Valerio Mariani; Carlo Lavalle; Marta Palombi; Nicola Pierucci; Sara Trivigno; Andrea D'Amato; Domenico Filomena; Pietro Cipollone; Domenico Laviola; Agostino Piro; Silvia Prosperi; Josefina Magliolo; et al. (ESC Heart Failure)
Abstract Background Sodium glucose cotransporter 2 inhibitors (SGLT2i) represent one of the four pillars of heart failure (HF) pharmacological therapy. Objective The study aims to clarify SGLT2i antiarrhythmic effect on patients with HF with reduced ejection fraction (HFrEF) in terms of atrial and ventricular arrhythmias (AAs and VAs) reduction. Methods HFrEF carriers of implantable cardioverter defibrillator (ICD) or cardiac resynchronization therapy defibrillator (CRT‐D) followed by remote monitoring of Policlinico Umberto I of Rome for 1 year before and after SGLT2i therapy initiation were enrolled in the study. We compared the incidence of AAs and VAs as recorded at remote monitoring during 1 year preceding SGLT2i therapy initiation and after 1 year of SGLT2i therapy. Results Among 198 enrolled patients, 135 patients had arrhythmic events before SGLT2i therapy prescription. There were 1353 arrhythmic events recorded in the year before SGLT2i therapy prescription, and 354 events were detected in the year after SGLT2i initiation, with a 73.8% reduction in events number after therapy initiation. After SGLT2i therapy initiation, the median number of total arrhythmic episodes significantly decreased from a median of 7 [3;12] to 1 [0;4] (P value < 0.001), AAs significantly decreased from a median of 4 [3;7] to 1 [0;3] episodes (P value < 0.001) and VAs were reduced from a median of 5.5 [3;10] to 0 [0;2] (P value < 0.001). When considering arrhythmia subtypes, larger reductions were recorded for atrial fibrillation (AF) episodes, reduced from 4 [3;8] to 0 [0;3], non‐sustained ventricular tachycardia (NSVT) that decreased from 4 [2;8.75] to 0 [0;2] (P value < 0.001) and for sustained ventricular tachycardia (SVT) that were reduced from 3 [2;4] to 0 [0;1] (P value < 0.001). Conclusions In HFrEF carriers of ICD/CRT‐D, the use of SGLT2i resulted in significant reduction of AA and VA events.